2015
DOI: 10.1038/ncb3251
|View full text |Cite
|
Sign up to set email alerts
|

Activator–inhibitor coupling between Rho signalling and actin assembly makes the cell cortex an excitable medium

Abstract: Animal cell cytokinesis results from patterned activation of the small GTPase Rho, which directs assembly of actomyosin in the equatorial cortex. Cytokinesis is restricted to a portion of the cell cycle following anaphase onset in which the cortex is responsive to signals from the spindle. We show that shortly after anaphase onset oocytes and embryonic cells of frogs and echinoderms exhibit cortical waves of Rho activity and F-actin polymerization. The waves are modulated by cyclin-dependent kinase 1 (Cdk1) ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

62
493
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 268 publications
(561 citation statements)
references
References 41 publications
62
493
4
2
Order By: Relevance
“…For example, the montage can reveal repetitive patterns in cortical waves of Rho activity and actin assembly–disassembly that might be overlooked when viewing the original movies (Bement et al, 2015). To make a montage, import the image stack and crop the area of interest by drawing a box and selecting “Image→Crop.” Then, create the montage by selecting “Image→Stacks→Make Montage” and specify the layout, scale, intervals, and increment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the montage can reveal repetitive patterns in cortical waves of Rho activity and actin assembly–disassembly that might be overlooked when viewing the original movies (Bement et al, 2015). To make a montage, import the image stack and crop the area of interest by drawing a box and selecting “Image→Crop.” Then, create the montage by selecting “Image→Stacks→Make Montage” and specify the layout, scale, intervals, and increment.…”
Section: Methodsmentioning
confidence: 99%
“…5). Using faster and higher resolution imaging, it was found that the Xenopus cortex continuously generates waves of Rho activity that stimulate subsequent waves of actin assembly and disassembly (Bement et al, 2015; Fig. 6; see also below).…”
Section: Introductionmentioning
confidence: 99%
“…At the single cell level, the collective dynamics of cortical actin have been documented in many cellular systems and are referred to as cortical waves. Understanding the cortical dynamics and the emergence of the collective dynamics within the cortex are critical for our understanding of cellular behaviours, such as polarity (Howell et al, 2012), migration (Weiner et al, 2007), mitosis (Bement et al, 2015), and cell growth (Das et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…For cortical actin waves, molecular players that act upstream of actin, including Rho family GTPases and their activating lipid second messengers have been heavily investigated. These include Rac and phosphatidylinositol-3,4,5-trisphosphate (PIP3) in HL-60 neutrophils (Weiner et al, 2007), Rho in Xenopus eggs and starfish oocytes (Bement et al, 2015), PIP3 and phosphoinositide-3-kinase (PI3K) in Dictyostelium discoideum (Arai et al, 2010), and Cdc42 and PI3K in RBL-2H3 mast cells (Xiong et al, 2016). Because waves of Rho GTPase activation usually precedes actin waves and inactivation of these Rho GTPases could abolish actin waves, activation of Rho GTPases has been suggested to be involved in wave nucleation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation